Towards the Professionalism Excellence of Teachers: Curriculum Management Transformation - Tuala, Riyuzen Praja; Ikbal, Ikbal; Fadillah, M Kharis (JURNAL AL-TANZIM, 2024)
This study aims to analyze curriculum management in improving teacher professional competence in madrasahs. The research method used is a qualitative case study type, where data is obtained through in-depth interviews, observations, and documentation. The results of the study indicate that effective curriculum management, which is reflected in the active involvement of teachers in constructive planning and supervision, has a substantial impact on improving teacher professional competence. However, this study also shows that there are weaknesses in the sense of creativity in the development of teaching materials and the use of learning media. Teacher competence can be improved through structured and inclusive curriculum management with technology integration in the learning process. This will provide new insights into formulating education policies for other madrasah. This study provides important implications for the development of curriculum management in madrasahs. With structured, inclusive curriculum management and the active involvement of teachers in every stage of planning, teacher professional competence can increase significantly.